The Effect of Caffeine Consumption on Reaction Time Among Medical Students of Universitas Tarumanagara Class of 2022–2023 - Anthon Eka Prayoga Khoto; Susy Olivia Lontoh (Lembaga Pengembangan Kinerja Dosen, 2025)
Caffeine is a commonly consumed stimulant known for its ability to enhance alertness and cognitive performance. One of its most extensively studied effects is its potential to reduce reaction time. However, existing research presents inconsistent findings regarding the effectiveness and duration of caffeine’s impact on cognitive speed.This study aimed to examine the effect of caffeine consumption on reaction time among medical students from the 2022 and 2023 cohorts at the Faculty of Medicine, Universitas Tarumanagara (FK UNTAR). A quasi-experimental design was employed using a comparative pre-test/post-test approach. The sample was selected through non-random consecutive sampling, without stratification. Inclusion criteria included being an academically active student in good physical and mental health.Reaction time was measured using the Ruler Drop Test before caffeine intake, and again at 15 and 30 minutes post-consumption. Data were analyzed using paired t-tests to assess within-group differences and independent t-tests to compare between groups.The results indicated a statistically significant reduction in reaction time following caffeine consumption (p < 0.05). The average reaction time before caffeine intake was 0.202 seconds, decreasing to 0.184 seconds at 15 minutes and 0.163 seconds at 30 minutes post-consumption. These findings suggest that the effect of caffeine on reaction time is most pronounced within 15–30 minutes after ingestion.